1995
DOI: 10.1113/expphysiol.1995.sp003852
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged alteration of vasoconstrictor and vasodilator responses in rat knee joints by adjuvant monoarthritis

Abstract: SUMMARYBoth neurogenic influences and the regulatory neuropeptide substance P (SP) have been implicated in the development of joint inflammation. Using the laser Doppler perfusion imaging technique to quantify relative changes in joint blood flow, the effects of nerve stimulation and topical SP application were examined in normal and chronically inflamed rat knee joints. Synovial inflammation was induced by unilateral intra-articular injection of Freund's complete adjuvant and experiments were carried out 1 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 12 publications
(18 reference statements)
3
48
0
3
Order By: Relevance
“…Along the same line as the present observation, McDougall et al reported the vasoconstriction response to electrical stimulation of sympathetic or saphenous nerves was diminished in rats with CFA-induced knee joint inflammation [13,14]. The vasoconstriction response to SS was reduced in rats with carrageenan inflammation as well [15].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Along the same line as the present observation, McDougall et al reported the vasoconstriction response to electrical stimulation of sympathetic or saphenous nerves was diminished in rats with CFA-induced knee joint inflammation [13,14]. The vasoconstriction response to SS was reduced in rats with carrageenan inflammation as well [15].…”
Section: Discussionsupporting
confidence: 88%
“…The vasoconstriction response to electrical stimulation of the sympathetic or saphenous nerve was diminished in a model of chronic inflammation induced by complete Freund's adjuvant (CFA) in rats [13,14]. Lam and Ferrell also reported the vasoconstriction response to electrical stimulation of the sympathetic nerve was reduced in carrageenan inflammation rats [15].…”
mentioning
confidence: 99%
“…This procedure is an accepted model for induction of chronic inflammations that produce rheumatoid arthritis like inflammatory reactions in human (Morgan et al, 1978;McDougall et al, 1995).…”
Section: Induction Of Chronic Inflammationmentioning
confidence: 99%
“…Finally, the animals were humanely killed by the high dose of urethane. The blood flow of biological zero level (BZL) of joint's tissue were recorded to subtract from the measured level during the experiment (McDougall et al, 1995).…”
Section: Measurement Of the Changes In Blood Flowmentioning
confidence: 99%
“…For example, Lundberg et al reported that electrical stimulation of the sympathetic nerve caused cutaneous vasodilatation in patients with obstructive vascular disease [5]. McDugall et al reported that the vasoconstriction response to electrical stimulation of sympathetic or saphenous nerves was diminished in rats with complete Freund's adjuvant (CFA)-induced knee joint inflammation [6,7]. Reduced vasoconstriction response to sympathetic nerve stimulation was also observed in rats with carrageenan inflammation [8].…”
mentioning
confidence: 99%